Serum biomarkers reflecting progression of knee osteoarthritis: a stage-based evaluation of TGF-?3, ADAMTS-4, ADAMTS-5, and MMP-13 - Esmez, Omer; Ercan, Zubeyde; Yilmaz, Secil; Dogru, Meryem Sedef (Bmc, 2026)
Background Knee osteoarthritis (KOA) is a progressive degenerative joint disease characterized by extracellular matrix (ECM) degradation and dysregulated inflammatory signaling. Identifying serum biomarkers associated with radiographic severity may improve early diagnosis, staging, and monitoring of progression. Objective To evaluate stage-dependent and non-linear changes in serum transforming growth factor-beta 3 (TGF-beta 3), ADAMTS-4, ADAMTS-5, and matrix metalloproteinase-13 (MMP-13) across Kellgren-Lawrence (KL) grades of KOA. Methods In this cross-sectional study, 200 participants were classified into five groups according to KL grade (KL0-KL4; n = 40 per group). Individuals with systemic inflammatory, metabolic, autoimmune, renal, cardiovascular, or bone metabolism-related disorders, and those using medications affecting cartilage or bone metabolism, were excluded. After overnight fasting, serum TGF-beta 3, ADAMTS-4, ADAMTS-5, and MMP-13 levels were measured by ELISA. Between-group comparisons were performed using one-way ANOVA or Kruskal-Wallis tests with appropriate post-hoc analyses, and data are presented as mean +/- standard deviation, unless otherwise stated. Results ADAMTS-4 differed significantly across KL grades (overall p < 0.00001), showing a non-linear pattern with higher levels in KL1-KL3. ADAMTS-5 demonstrated a pronounced stage-dependent pattern (overall p < 0.00002), peaking in KL1 and declining toward advanced stages. Serum MMP-13 levels did not differ significantly across KL grades (p > 0.05). TGF-beta 3 levels differed significantly across KL grades (overall p = 0.0015), with lower levels in KL1-KL2 compared with KL0 and intermediate levels in KL3-KL4. Conclusions ADAMTS-4 and ADAMTS-5 exhibit biphasic, stage-dependent changes during KOA progression, consistent with early enzymatic activation followed by late-stage reduction. Early declines in TGF-beta 3 may reflect impaired cartilage homeostasis. The observed non-linear, stage-dependent serum patterns-particularly for ADAMTS-4, ADAMTS-5, and TGF-beta 3-highlight dynamic extracellular matrix remodeling during KOA progression and support the potential value of serum biomarkers as adjuncts to radiographic staging, especially in early disease.
Keywords: Knee osteoarthritis; Serum biomarkers; ADAMTS-4; ADAMTS-5; MMP-13; TGF-beta 3; Kellgren-Lawrence grading